Effect of Giving Growth Regulatory Substances (ZPT) Superior Plant Hormones (Ghosts) on Growth and Yields of Shallots (Allium Ascalonicum L) - Bambang Wicaksono Hariyadi; Sutriyono; Mahrus Ali (Faculty of Agriculture, Merdeka University Surabaya, 2020)
purpose of this study was to determine the extent of the effect of the provision of GH growth regulators on growth and yield in onion plants. This research was conducted in the Research Field of the Faculty of Agriculture, Merdeka University, Surabaya from April to June 2019. This study used a Randomized Block Design (RBD) consisting of six treatments of GHOS, with three replications and using two sample plants. Use of ZPT Ghost fertilizer at doses Z = without fertilizer / control, Z1 = 1 ml / l / plant, Z2 = 2 ml / l / plant, Z30 = 3 ml / l / plant, Z = 4 ml / l / plant, and Z = 5 ml / l / plant. Observations made consisted of plant length, number of leaves, plant wet weight, plant tuber weight, and number of plant tuber. The results showed that the treatment of GHOS ZPT dose significantly affected all observed variables, namely plant length, number of leaves, number of tubers, plant wet weight and tuber weight of onion (Allium ascalonicum L.). The treatment of GHOS dose of 5ml per liter of water showed the highest growth and yield with a plant length of 30.16 cm, number of leaves 46.00, plant wet weight 68.33 grams, plant tuber weight 49.00 grams, and number of plant tubers 10 , 00 although statistically not significantly different from the ZPT GHOS fertilizer treatment using a dose of 1ml per liter of water with a plant length of 29.00 cm, number of leaves 34.83, plant wet weight 58.16 grams, plant tuber weight 38.56 grams and number of plant tubers 8,16.